Hubungan antara amalan pengurusan keselamatan dengan pematuhan keselamatan di Jabatan Pengairan dan Saliran (JPS) negeri Perak - Muhammad Afif, Halim (2017)
This study intended to examine the relationship work safety practices and safety compliance. A work safety practice is namely management commitment, safety training, employee engagement, communication and feedback in safety, regulatory and safety procedures and safety promotion. A research framework was developed, and seven hypotheses were posited and tested. The study was based on a survey design and cross sectional. From 350 questionnaires distributed, 337 questionnaires were collected from JPS Perak staff and were used in subsequent statistical analyses. The study hypotheses were tested using correlation and regression analyses. Pearson correlations analysis indicated that all the independent variable (management commitment, safety training, employee engagement, communication and feedback in safety, regulatory and safety procedures, safety promotion) showed a positive relationship exists with dependent variable (safety compliance). Results of multiple regression analysis shows only safety communication and feedback and management commitment influence towards safety compliance. In conclusion, this study provided insight and further understanding of the interrelationship between work safety practices and safety compliance, and hence allows Jabatan Pengairan dan Saliran (JPS) to gain in depth knowledge about the impact of work safety practices on safety compliance.